2017
DOI: 10.1177/1010428317695022
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of long noncoding RNA zinc finger antisense 1 enhances epithelial–mesenchymal transition in vitro and predicts poor prognosis in glioma

Abstract: Increasing evidence indicates that long noncoding RNAs play important roles in development and progression of various cancers. Zinc finger antisense 1 is a novel long noncoding RNA whose clinical significance, biological function, and underlying mechanism are still undetermined in glioma. In this study, we reported that zinc finger antisense 1 expression was markedly upregulated in glioma and tightly correlated with clinical stage. Moreover, patients with high zinc finger antisense 1 expression had shorter sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 33 publications
4
42
0
1
Order By: Relevance
“…Previous reports have shown that ZFAS1 is highly expressed in glioma tissues and cells, and ZFAS1 downregulation significantly inhibits glioma cells proliferation, migration, and invasion, and it accelerates apoptosis. 39,40 The expression of ZFAS1 is downregulated in breast cancer and acts as a tumor-suppressive gene; 41 in contrast, ZFAS1 is upregulated in colorectal, gastric, hepatocellular, bladder, and ovarian cancers, acting as an oncogene; and ZFAS1 is dysregulated in various malignant tumors and is involved in tumor proliferation, invasion, metastasis, apoptosis, cell cycle, and drug resistance. 42 Many proteins interact with the transcribed RNAs to form RNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that ZFAS1 is highly expressed in glioma tissues and cells, and ZFAS1 downregulation significantly inhibits glioma cells proliferation, migration, and invasion, and it accelerates apoptosis. 39,40 The expression of ZFAS1 is downregulated in breast cancer and acts as a tumor-suppressive gene; 41 in contrast, ZFAS1 is upregulated in colorectal, gastric, hepatocellular, bladder, and ovarian cancers, acting as an oncogene; and ZFAS1 is dysregulated in various malignant tumors and is involved in tumor proliferation, invasion, metastasis, apoptosis, cell cycle, and drug resistance. 42 Many proteins interact with the transcribed RNAs to form RNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Then, knockdown of ZFAS1 in glioma cell lines significantly suppressed proliferation, migration and invasion. Lv et al [26] reported that ZFAS1 expression was markedly upregulated in glioma tissues and tightly correlated with clinical stage and shorter survival. Then they found knockdown of ZFAS1 in glioma cell lines could promote apoptosis, and inhibit cell proliferation, migration, and invasion.…”
Section: Zfas1 In Various Cancersmentioning
confidence: 99%
“…It has been demonstrated that ZFAS1 could regulate the expression of above gene, thus promote the tumorgenesis and progression of various cancers such as melanoma, glioma, colorectal cancer and gastric cancer [26, 30, 37, 47]. However, whether these effect are direct or indirect, is unknown until now.…”
Section: Regulatory Mechanisms Of Zfas1 In Human Cancersmentioning
confidence: 99%
“…However, there were opposite findings that elevated lncRNA ZFAS1 occurred in gastric cancer, hepatocellular carcinoma and glioma. The function of lncRNA ZFAS1 in cancer cells might be cell type-dependent [12][13][14][15][16][17][18][19][20]. Therefore, we need a systematical and comprehensive meta-analysis to explore whether overexpression of ZFAS1 in tumor are related to worse outcome.…”
Section: Oncotarget 2 Wwwimpactjournalscom/oncotargetmentioning
confidence: 99%
“…According to the inclusion and exclusion criteria, 747 patients from 8 eligible studies were included in this meta-analysis [12][13][14][15][16][17][18][19]. The screening process was shown in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%